2005
DOI: 10.1016/j.jad.2005.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of trauma-related guilt following treatment of PTSD in female rape victims: A result of cognitive processing therapy targeting comorbid depression?

Abstract: Background and methods-Although Resick et al. (2002) [Resick, P.A., Nishith, P., Weaver, T.L., Astin, M.C., Feuer, C.A., 2002. A comparison of cognitive-processing therapy with prolonged exposure and a waiting condition for the treatment of chronic posttraumatic stress disorder in female rape victims. J. Consult. Clin. Psychol. 70,[867][868][869][870][871][872][873][874][875][876][877][878][879] reported comparable results for treating raperelated posttraumatic stress disorder (PTSD) using either cognitive-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 23 publications
3
61
0
1
Order By: Relevance
“…Trauma-related guilt cognitions, such as false beliefs about responsibility or pre-outcome knowledge, are reliably associated with symptoms of depression among diverse samples of trauma survivors (Blacher 2000;Kubany et al 1995Kubany et al , 2004Lee et al 2001). Moreover, cognitive processing therapy and prolonged exposure interventions appear to be effective at reducing trauma-related guilt cognitions (Nishith et al 2005, Resick et al 2002.…”
Section: New Directions In Research On Shame and Guiltmentioning
confidence: 98%
“…Trauma-related guilt cognitions, such as false beliefs about responsibility or pre-outcome knowledge, are reliably associated with symptoms of depression among diverse samples of trauma survivors (Blacher 2000;Kubany et al 1995Kubany et al , 2004Lee et al 2001). Moreover, cognitive processing therapy and prolonged exposure interventions appear to be effective at reducing trauma-related guilt cognitions (Nishith et al 2005, Resick et al 2002.…”
Section: New Directions In Research On Shame and Guiltmentioning
confidence: 98%
“…Studies have found guilt to be strongly associated with PTSD among combat veterans, battered women, and rape victims (Beckham, Feldman, & Kirby, 1998;Henning & Frueh, 1997;Kubany et al, 1995Kubany et al, , 1996Nishith, Nixon, & Resick, 2005). Leskela, Keipering, and Thuras (2002) found former prisoners of war with PTSD were more likely to have shame, but not guilt.…”
Section: Emotions and The Maintenance Of Posttraumatic Stress Disordermentioning
confidence: 99%
“…During the last few years, a growing number of studies [15,22,24,25,26] have indicated that cognitive behavioural therapy elements may be effective in the treatment of child abuse-related PTSD, especially in reducing feelings of guilt and shame, which are complex PTSD symptoms. The guideline of the International Society for Traumatic Stress Studies [12] stated that patients with an inability to tolerate strong affects should initially focus on ‘stabilization’, so-called phase-based treatment [27].…”
Section: Introductionmentioning
confidence: 99%